Is it time to measure complications from the National Trauma Data Bank? A longitudinal analysis of recent reporting trends. Issue 2 (February 2019) - Robles, Anamaria J.; Conroy, Amanda S.; Cohen, Mitchell J.; Callcut, Rachael A.
Abstract : BACKGROUND: Payers have approached select complications as never events, yet there is rationale that achieving a zero incidence of these events is impractical. Prior 2005 National Trauma Data Bank (NTDB) analysis showed high rates (37%) of centers reporting no complications data making national estimates for determining standardized complication rates difficult to ascertain. METHODS: The 2008–2012 NTDB National Sample Program nationally weighted files were used to calculate yearly national estimates. Rates were compared in all centers and those reporting complications data. Hospital characteristics were compared using Student t test. In 2011, an other complication category was introduced; overall rates were calculated with and without this category. Yearly estimates were reported for patients receiving care within centers reporting complications data. RESULTS: From 2008–2012 NTDB, there were raw data on 3, 657, 884 patients. A total of 594, 894 patients (16.3%) experienced one or more complications (82.7% one complication; 17.3% two or more complications). Excluding the other complication category, the overall weighted rate was 8.4% to 9.2%. Pneumonia was the most common complication (2.7–3.0%), occurring at twice the 2005 rate. The number of centers reporting no complications data dropped to 8.1% in 2011 (2008, 14.5%; 2009, 18.2%; 2010, 15.9%; 2012, 8.9%). By 2012, nearly all level I centers reported complications, whereas 46.4% of level IVs reported none (I 0.5%, II 2.7%, III 8.5%, p = 0.04). Data were reported the least frequently in nonteaching hospitals (15.8%, p = 0.007), those in the South (19.6%, p = 0.007), and those with less than 200 beds (23.6%, p = 0.005). CONCLUSION: Overall rates of complications from 2008 to 2012 were nearly twofold higher than 2005 data. Reporting has increased, and NTDB may provide a valuable platform for establishing rational and achievable measures for specific complications. LEVEL OF EVIDENCE: Prognostic and epidemiological, level IV. Abstract : Supplemental digital content is available in the text.